Soft law versus hard law: Critiquing the categorisation of sources of international law from a third world perspective - Seneviratne, S.S.M.W. (Faculty of Law, University of Colombo, 2021)
Effective implementation of international law has been challenging, given the distinctive characteristics of international law. Categorisation of international law sources as soft and hard law aggravates the lapses in enforcement. This research examines the aptness of this categorisation from a third world perspective. Researcher argues that this divide is arbitrary and used by powerful States to achieve their geo-political interests against less powerful States. Credence and authority attached to hard laws as opposed to soft laws discourage States in contributing to their enforcement. International law makers create a boundary between hard and soft laws. It may dissuade the law takers as they may perceive the classification as a regulator. Sovereign States prefer to follow soft laws than hard laws mainly due to the desire to preserve their political independence and territorial integrity from international scrutiny led by powerful States. Particularly, States, belonging to the ‘third world’ camp, are reluctant to be bound by certain hard laws to avoid perceived geo-political dominations. Researcher further argues that such a behaviour is not at fault as the unequal application of international law challenges its foundational principles, such as sovereignty and equality of States. This attitude may hinder effective enforcement of international law. Collapse of law and order in several countries, such as in Afghanistan and Guinea, provide examples about the unfounded classifications of international law, manipulated for the gain and control of powerful States. Underlying western plots attest to the soundness of this argument when one carefully examines the history of such situations. This research is a doctrinal analysis based on the critical body of work developed by ‘third world approaches to international law scho1arship’(TWAIL) and discusses selected case studies as its methodology.
Keywords: soft law; hard law; sources of international law; third world approaches to international law (TWAIL)